Enhancing Pest Management Knowledge and Skills for Young Researchers and NPPOs in WANA and East Africa Regions - Kumari, Safaa; Nazari, Kumarse; Boulamtat, Rachid; Moukahel, Abdulrahman; Maafa, Ilyass; Kemal, Seid Ahmed (International Center for Agricultural Research in the Dry Areas, 2024)
As cross cutting activities, training provided by three work packages (WP1, WP2 & WP3) during 2023/24 are reported under WP3-OP3. The internship opportunities were given to nine young students who recently finished their studies in plant protection. A total of 25 graduate students (9 MSc and 16 PhD) from 6 countries Ethiopia, Lebanon, Morocco, Syria, Tunisia, and Türkiye) are doing parts of their theses research at ICARDA research platforms in Türkiye, Morocco, Lebanon and Ethiopia. Graduate student Theses research focuses on parasitic weeds, detection using modern diagnostic techniques, and management of viruses and insect pests of food legumes. The knowledge generated from graduate students will be useful in managing pests and diseases of PHI targeted pests on key staple food crops. In addition, 10 NPPOs experts (8 females) from Lebanon and Morocco attended a training course for 1-2 weeks on IPDM, detection and identification of wheat and food legume diseases.